Effects of self-selected vs prescribed repetition configurations on force, velocity and power variables in a back squat. - Ball, N.; Ibbott, P.; Norcott, B. (Journal of Australian Strength and Conditioning, 2017)
Strength is a key component in athletic development and can be varied using acute variables such as recovery, reps and sets and load. One method to manipulate these is to allow the athlete to self-select the variable to accommodate for day-day variations, seek training time efficiency and allow increased focus. No study has investigated the effect of self-selecting repetitions and sets in a trained population. This study aimed to assess the effect of self-selecting repetitions and sets to complete 15 repetitions of a back squat. 8 trained junior athletes completed two testing sessions, one prescribed 3 sets by 5 reps with 2 minutes` recovery (PRES) and 1 self-selected (SS) condition. Force, velocity and power variables were recorded using a GymAware linear encoder in each repetition. Paired sample t-tests and linear regressions were used for analysis of between and within conditions. Results showed that all athletes self-selected a different repetition and set configuration compared to the prescribed condition. However, the SS condition had significantly lower force, velocity and power values compared to the prescribed conditioning (<0.05). Within each condition a majority of variables showed no significant increases or decreases between first and last repetitions, indicating a similar output as repetitions progressed. Self-selecting repetition and sets in a trained junior rugby population does not improve the force, power and velocity output in a back squat compared to a more traditional prescribed repetition and sets configuration. Self-selecting may provide a suitable short-term training stimulus to vary training sessions based on no decrease in variables within the set; however, for this purpose cluster training would be more beneficial to enhance kinetic output.